2009
DOI: 10.1007/s12648-009-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental understanding and modeling of spin coating process: A review

Abstract: : A mathematical model is derived to elucidate the dominant mechanism governing film formation. It leads to a relation between film thickness and film radius spreading with time. Inclusion of evaporation and shear stress was made with extension to non-Newtonian fluid. The advantages and disadvantages of this process with applications are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
211
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(236 citation statements)
references
References 6 publications
0
211
0
4
Order By: Relevance
“…The approach to achieve homogeneity in the layer thickness and distribution required several optimisation cycles of SPEEK polymer dissolved and dropped on a silicon wafer. The viscosity and surface tension of dissolved SPEEK, could cause non-homogenous film distribution, therefore a plasma etching [59] procedure was carried out on the silicon wafers to improve affinity between the wafer and the substrate as SPEEK flow on a flat spinning substrate is one of the most important physical processes involved in SC [56] , [57]. The election of the solvent is fundamental for homogenous coating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach to achieve homogeneity in the layer thickness and distribution required several optimisation cycles of SPEEK polymer dissolved and dropped on a silicon wafer. The viscosity and surface tension of dissolved SPEEK, could cause non-homogenous film distribution, therefore a plasma etching [59] procedure was carried out on the silicon wafers to improve affinity between the wafer and the substrate as SPEEK flow on a flat spinning substrate is one of the most important physical processes involved in SC [56] , [57]. The election of the solvent is fundamental for homogenous coating.…”
Section: Resultsmentioning
confidence: 99%
“…[5,48,54] Consequently, preparing SPEEK polymeric thin films (PTFs) by spin coating (SC) offers a novel type of polymeric support for IMS. SC is currently a predominant technique used to produce uniform thin films of organic materials with customized thicknesses of the order of micrometres and nanometres [55] , [56] , [57]. MNPs applications depend on their distribution, as well as the density of MNPs over the support.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the spinning process appears to be managing the time-evolution of the volume, composition and evaporation rate of the solution. [34] We plot in Figure 2a the evolution of the solution thickness calculated from the combined optical measurements throughout the 30 s duration of spin-coating, including the increase of spin-speed from 700 rpm at the 10 s mark. We observe a rapid decrease of the solution thickness from ca.…”
Section: In-situ Investigation Of the Spin-coating Processmentioning
confidence: 99%
“…Later, in 1978, Meyerhöfer reported that the dispersion caused by centrifugal force was mostly responsible for the thickness of the resultant film, nevertheless from a certain moment the film thickness was determined mainly by solvent evaporation 19 . The spin coating has some stages: the solution is deposited on the blade, the blade is accelerated until the stabilization of the adjusted rotation resulting in a uniform speed and finally, the solution ceases to be expelled by centrifugal force and the thickness control is accomplished only by solvent evaporation 20 . Figure 2 shows the complete spin coating process.…”
Section: Introductionmentioning
confidence: 99%